PROBLEM OF ELERCTRIC ENERGY EFFICIENCY POTENTIAL EVALUATION OF UNDERGROUND IRON-ORE PRODUCTION - Synchuk, Oleg; Guzov, Eduard; Yalovaya, Olena (Scientific Works of Vinnytsia National Technical University, 2015)
The paper contains the analysis of energy consumption volumes at iron-ore production enterprises with underground method of mining. The research shows that electric energy presents about 90% of all energy expenditures. Ways of enhancement of electric energy efficiency at these mining enterprises are considered. The structure of energy saving potential for iron-ore production is suggested. Recommendations, aimed at the improvement of energy efficiency of underground iron-ore productions are given. REFERENCES 1. Основи енергозберігаючого керування електроенергетичними системами та комплексами / [Сінчук О. М., Сінчук І. О., Федорченко Н. А., Мельник О. Є. та ін.] – Кременчук: Вид. ПП Щербатих О. В., 2010. – 340 с. 2. Гойхман В. М. Регулирование электропотребления и экономия электроэнергии на угольных шахтах / В. М. Гойхман, Ю. П. Миновский. – М.: Недра, 1988. – 320 с. 3. Комбинаторика преобразователей напряжения современных тяговых электроприводов рудничных электровозов / [Синчук О. Н., Синчук И. О., Юрченко Н. Н., Чернышов А. А., Удовенко О. А., Пасько О. В., Гузов Э. С.] – Київ: ІЕДНАНУ, 2006. – 252 с. 4. Синчук О. Н. Совершенствование методов расчёта электрических нагрузок при проектировании и модернизации систем электроснабжения железорудных предприятий / О. Н. Синчук, Э. С. Гузов, Р. А. Пархоменко // Вісник Кременчуцького національного університету. – 2013. – Вип. 1 (78). – С. 28 – 32.